Bournville-Relaunch in India: A Case Study - Sinha, Nilanjana; Dasgupta, Rajkumar (Indian Journal of Marketing, 2010)
Bournville is one of the legendary dark bitter chocolates mostly famous in UK and west European countries. It was re-launched in India in October 2008 with much pomp, vanity and galore. The Company perhaps thought that it can cater to the niche segment which is fond of the bitter taste and used to buy it from outside India. After the gala launch and ambitious ad campaign, not much ice was melted. For most of the consumers, the taste did not suit their palate. Moreover, the Indian psyche does not permit to buy a product which is bitter and dark and can be presented to others in any special occasion. The 'mumbo-jumbo' ad of Bournville is perhaps a little too overboard for most of the Indian target audience. They could not relate the ad with their Indian mentality. After the initial euphoria in the market, where consumers used to buy it enthusiastically and with much expectation, the Company's efforts seems to fall flat in the market. A survey of management students was conducted in this regard to confirm the causes of the dismal performance of the brand.